CALPHAD-Based Thermodynamic Modeling in Welding and Joining Processes: Applications and Technical Implications - Kim, Young-Min; Hwang, Insung (Journal of Welding and Joining, 2025)
The CALPHAD (CALculation of PHAse Diagrams) method has emerged as a powerful tool for quantitatively analyzing phase transformations, diffusion, and microstructural evolution in multicomponent alloy systems. While traditionally applied in alloy design and heat treatment optimization, its application to welding and joining processes is expanding, especially under non-equilibrium thermal conditions. This study provides a systematic overview of CALPHAD-based thermodynamic modeling applied to welding and joining technologies. The processes are categorized into fusion-based and solid-state-based types, and the use of CALPHAD to simulate solidification behavior, intermetallic compound formation, reaction layer growth, and heat-affected zone (HAZ) transformations is discussed. Coupled tools such as DICTRA and TC-PRISMA are also reviewed for time-dependent diffusion and precipitation analysis. Recent research highlights that CALPHAD enables predictive control of joint microstructure and performance, particularly in dissimilar material joining and advanced alloy systems. This paper outlines key application strategies and discusses the integration potential with AI-driven process optimization in future manufacturing environments.